Vitamin D3 Priming of Dendritic Cells Shifts Human Neutrophil-Dependent Th17 Cell Development to Regulatory T Cells - Hafkamp, Florianne M. J.; Taanman-Kueter, Esther W. M.; van Capel, Toni M. M.; Kormelink, Tom Groot; de Jong, Esther C. (Frontiers in Immunology, 2022)
Vitamin D3 (VD3) is a potential adjuvant for use in tolerogenic vaccine formulations that target dendritic cells (DCs) for the treatment of chronic inflammatory disorders, e.g. autoimmune diseases. These disorders are often associated with enhanced activity of IL-17-producing T helper 17 (Th17) cells which develop in a DC-driven and neutrophil-dependent fashion. Here, we investigated the effect of VD3 on Candida albicans-specific human T cell differentiation, since C albicans is a model pathogen for Th17 cell development. VD3-priming of DCs restricted neutrophil-dependent Th17 cell development and neutrophil-independent Th1 cell formation from naive CD4+ T cells. In line with this, production of Th1/Th17 polarizing cytokines IL-12 and IL-23 by DCs was reduced by VD3-priming. Development of both FoxP3+CD127lowCD25+ Tregs and IL-10-producing T cells was significantly enhanced in VD3-primed conditions, even in presence of neutrophils. ICOS+ Tregs, major IL-10 producers, CD69+FoxP3+ and TIGIT+FoxP3+ Tregs were significantly induced by VD3-priming as well. Our data support the potential use of VD3 as adjuvant to induce tolerance in treatment of autoimmune disorders, including those in which neutrophils are involved in the pathogenesis, since we show that Treg development is enhanced by VD3 even in presence of neutrophils, while Th17 cell development is restricted.